(untitled) (Journal of Applied Oral Science, 2011)
OBJECTIVE: The aims of this study were to investigate the effectiveness of sealant placement under the guidelines of the Oral Health Promotion Program for Children and Adolescents (Portugal), and to test the influence of clinical and socioeconomic variables on the DMFT increment in 277 children, born in 1997. MATERIAL AND METHODS: A dental hygienist performed the initial examinations and sealant placement (Helioseal, Vivadent) on the permanent first molars in 2005. These activities were registered in dental records that were assessed in 2007. Children were classified according to caries risk at baseline [high (HR: DMFT+dmft>;0); low (LR: DMFT+dmft=0) risk] and sealant placement as follows: HR-S and LR-S Groups (with sealant placement); HR-NS and LR-NS Groups (without sealant placement). A calibrated dentist performed the final examination in 2007 at school, based on the World Health Organization recommendations. The variables collected were: dental caries, visible dental plaque, malocclusions, and socioeconomic level (questionnaire sent to children's parents). For univariate (Chi-square or Fisher tests) and multivariate (Multiple logistic regression) analyses the DMFT increment >;0 was selected as dependent variable. RESULTS: Approximately 17.0% of the children showed DMFT increment>;0 (mean=0.25). High-risk children presented a significant increase in the number of decayed and/or filled teeth. These children had 7.94 more chance of developing caries. Children who did not receive sealant were 1.8 more prone to have DMFT increment >;0. CONCLUSION: It appears that sealant placement was effective in preventing dental caries development. Moreover, the variables "risk" and "sealant placement" were predictors for DMFT increment in the studied children.